Questionnaire as a Tool for Assessment of Interanal Control System against Coso Internal Control – Integrated Framework (International Journal of Scientific Research and Management (IJSRM), 2021)
The article deals with the scientific and practical aspects of the transparency of internal control. The urgency of the topic of this article is caused by the need for analysis and the search for a mechanism for assessing the effectiveness of conducting internal control at the enterprise. The article examines the imperatives of internal control, as well as substantiates the main conceptual foundations of the organization of internal control. The article proposes an approach to assessment of enterprise internal control system against the COSO – Internal Control – Integrated Framework.